The regulation of telecommunication in the United Kingdom of Great Britain & Northern Ireland - Ewan Sutherland (International Telecommunications Society (ITS), 2011)
This paper reviews the application of national antitrust law and the implementation of the European Union's telecommunications directives to the markets in the United Kingdom, against the declared policy objective of raising national competitiveness. It illustrates the complexity of the systems that have been created over three decades, with complex and interlocking regulatory, self-regulatory, judicial and appellate bodies, interacting with the parliamentary systems to form a regulatory state. Where markets have failed, or thought likely to fail, the state at different levels (UK, national and municipal) has supported studies and subsidized the provision of broadband Internet access. The regulator, using its sectoral antitrust powers, agreed with British Telecom to functional separation, transferring the enduring bottleneck of local access to a separate subsidiary. While the UK describes itself as a regulatory leader this is difficult to evaluate, given the number and the frequencies of changes, nonetheless the claim seems very difficult to substantiate.
Keywords: 330; Governance; Competitiveness; Regulatory state; Great Britain; United Kingdom